FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN UMUR MENARCHE PADA SISWI SMP NEGERI 1 SEI RAMPAH KAB. SERDANG BEDAGAI TAHUN 2016 - balqis fadillah; Rahayu Lubis; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Menarche was the first menstruation cycle experienced by women. While early menarche first menstruation occured is under the age of 12 years. Based on the result oh Health Research Association (Riskesdas) in 2010, that 5,2 % of children in 17 provinces in Indonesia experienced menarch under the ages of 12 years. Early menarch is a risk factor for malignant disease. The purpose of  this research was to determine the factors-factors related with the ages of menarche in female students of  SMP Negeri 1 Sei Rampah  in 2016. This research is an observational study with cross sectional research design. Age of menarche is a dependent variable in this study, while the diet, nutritional status, physical activity, and age of menarche mother is an independent variable Sample was many 114 students were taken by purposive sampling. The research instrumen used was a questionnare as well as  the scale of measuring instruments and gauges. Univariat data were analyzed descriptive andbivariat data were analyzed using the chi square test with 95 % CI. The result showed prevalence of early menarche in SMP Negeri 1 Sei Rampah in 2016  the highest of the ages normal menarche is (67,5%), and early menarch is (32,5%). The average ages og menarch is 11,89 years with the highest ages of menarch is 13 years and lowest is 10 years. The highest of the responden is bad habit diet (65,8%), not obest nutritional status (87,7%), enough fisic activity (64,9%), and mother’s ages of menarch is normal (79,8%). The result of bivariate analysis, generally there is a significant relationship habit diet (p=0,017), nutritional status (p=0,007), physical activity (p=0,003), mother’s ages of menarche (p=0,0001). It is suggested to students of SMP Negeri 1 Sei Rampah who have early menarche to maintain healthy lifestyle so that risk factors for malignant disease such as ovarian cancer, breast cancer, utery myomas, menopause can be minimized.